PENERAPAN MODEL SKEMP DALAM PEMBELAJARAN SOAL CERITA MATEMATIKA DI SEKOLAH DASAR - Martianty Nalole (Jurnal Inovasi, 2008)
According to expert in mathematics, the story of mathematics in primary school is very difficult for student. The goal of this to know implementation of scheme model can increase achievement of student learning, especially to solve the question of the story. The focus of this writing is essential of student subject, problem solving, story, and Skemp model.